HR TECHNOLOGIES AS DIGITAL TRANSFORMATIONS OF COMPANIES IN THE USA, JAPAN AND EUROPE (Development Service Industry Management, 2024)
Ukrainian business leaders, like their Western counterparts, face the need to adapt to new realities and implement innovative HR technologies. To this end, the authors offer a number of specific recommendations based on the experience of different countries. The authors describe international experience and challenges of effective management of insurance companies in the world in the context of the pandemic crisis, which is relevant for many companies in the market.American companies are leaders in innovative HR technologies such as artificial intelligence, machine learning, and big data. They actively use these technologies to automate routine tasks, analyze data, and make data-driven decisions.Japanese companies are known for their focus on developing human capital and creating long-term relationships with employees. They combine traditional approaches to human resources management with modern technologies such as mentoring systems and 360-degree assessments.European companies pay great attention to data protection and employee privacy. They are actively implementing technologies that ensure the security of personal data and the trust of European employees.The experience of HR digital transformation in the USA, Japan, and Europe is valuable for Ukrainian companies. By studying these cases, Ukrainian companies will be able to: identify best practices and adapt them to their needs; avoid common mistakes when implementing new technologies; and accelerate the process of digital HR transformation.The cases of: an insurance company in the United States as a leader in innovative HR technologies; a Japanese insurance company - a combination of traditions and digital innovations; the case of an insurance company in Europe “Forinsurer” is considered.Recommendations for Ukrainian enterprises: to audit existing HR processes and identify areas for the introduction of new technologies; to develop a digital HR transformation strategy that meets business goals; to involve all employees in the transformation process; to choose technologies that meet the scale and needs of the company; to regularly evaluate the effectiveness of the implemented technologies and make the necessary adjustments.
Keywords: HR digital transformation; leadership technologies; human resource management; HR technologies; foreign experience; Ukrainian enterprises